Curcumin-Artesunate Based Polymeric Nanoparticle; Antiplasmodial and Toxicological Evaluation in Murine Model - Oyeyemi, Oyetunde; Morenkeji, Olajumoke; Afolayan, Funmilayo; Dauda, Kabiru; Busari, Zulaikha; Meena, Jairam; Panda, Amulya (Frontiers in Pharmacology, 2018)
Mainstay chemotherapy for malaria is often faced with the problem of instability and poor bio-distribution thus resulting in impaired pharmacokinetics. Nanomedicine has been acclaimed for its success in drug delivery and improved efficacy. The aim of the study was to assess the antiplasmodial efficacy and safety of curcumin-artesunate co-entrapped nanoparticle in mice model. Curcumin (C) and artesunate (A) were loaded in poly (D,L-lactic-co-glycolic acid) (PLGA) using solvent evaporation from oil-in-water single emulsion method. The nanoparticle formed was characterized for size, polydispersity index, zeta potential and entrapment efficiency. The in vitro release of the drug was also determined. The in vivo antiplasmodial activity of CA-PLGA nanoparticle was tested on Plasmodium berghei at 5 and 10 mg/kg doses. The drug efficacy was determined at day 5 and 8. Hematological and hepatic toxicity assays were performed. The mean particle size of drug entrapped PLGA-nanoformulation was 251.1±12.6 nm. The drug entrapment efficiency was 22.3±0.4%. There was a sustained drug release from PLGA for 7 days. The percentage suppression of Plasmodium berghei was consistently significantly higher in CA-PLGA 5 mg/kg at day 5 (79.0%) and day 8 (72.5%) than the corresponding values 65.3 and 64.2% in the positive control group (p <0.05). Aspartate aminotransferase (AST) was significantly lower in mice exposed to 5 mg/kg (42.0±0.0 U/L) and 10 mg/kg (39.5±3.5 U/L) nanotized CA-PLGA compared with the negative control (45.0±4.0 U/L) (P<0.05). Although the alanine aminotransferase (ALT) was lower in nanotized CA-PLGA, the variation was not significant compared with the negative control (P>0.05). No significant difference in the mean values of the different blood parameters in all exposed groups with the exception of platelets which were significantly higher in the positive control group. A simple method of dual entrapment of curcumin and artesunate with better antiplasmodial efficacy and low toxicity has been synthesized.